Folding correction of ABC‐transporter ABCB1 by pharmacological chaperones: a mechanistic concept. Issue 3 (26th May 2017) - Spork, Matthias; Sohail, Muhammad Imran; Schmid, Diethart; Ecker, Gerhard F.; Freissmuth, Michael; Chiba, Peter; Stockner, Thomas
Abstract: Point mutations of ATP‐binding cassette (ABC) proteins are a common cause of human diseases. Available crystal structures indicate a similarity in the architecture of several members of this protein family. Their molecular architecture makes these proteins vulnerable to mutation, when critical structural elements are affected. The latter preferentially involve the two transmembrane domain (TMD)/nucleotide‐binding domain (NBD) interfaces (transmission interfaces), formation of which requires engagement of coupling helices of intracellular loops with NBDs. Both, formation of the active sites and engagement of the coupling helices, are contingent on correct positioning of ICLs 2 and 4 and thus an important prerequisite for proper folding. Here, we show that active site compounds are capable of rescuing P‐glycoprotein (P‐gp) mutants ∆Y490 and ∆Y1133 in a concentration‐dependent manner. These trafficking deficient mutations are located at the transmission interface in pseudosymmetric position to each other. In addition, the ability of propafenone analogs to correct folding correlates with their ability to inhibit transport of model substrates. This finding indicates that folding correction and transport inhibition by propafenone analogs are brought about by binding to the active sites. Furthermore, this study demonstrates an asymmetry in folding correction with cis‐flupentixol, which reflects the asymmetric binding properties of this modulator to P‐gp. Our results suggest a mechanistic model for corrector action in a model ABC transporter based on insights into the molecular architecture of these transporters.